Public preferences for involvement in the governance of health data - De Freitas, Cláudia (2020)
Public involvement in the governance of epidemiological and public health studies can foster needs-driven research, enhance participants' recruitment, reduce attrition and improve the quality of and ethics in research and surveillance. However, it can also reinforce health inequalities if it fails to ensure public representation across socioeconomic gradients. This study aimed to assess patients' and carers' preferences for involvement in collective health data governance, and its associated factors, to strengthen the evidence base for policy development.